Gold nanoparticles interfere with sperm functionality by membrane adsorption without penetration. Issue 1 (August 2014) - Taylor, Ulrike; Barchanski, Annette; Petersen, Svea; Kues, Wilfried August; Baulain, Ulrich; Gamrad, Lisa; Sajti, Laszlo; Barcikowski, Stephan; Rath, Detlef
Abstract To examine gold nanoparticle reprotoxicity, bovine spermatozoa were challenged with ligand-free or oligonucleotide-conjugated gold nanoparticles synthesized purely without any surfactants by laser ablation. Sperm motility declined at nanoparticle mass dose of 10 µg/ml (corresponding to ∼14 000 nanoparticles per sperm cell) regardless of surface modification. Sperm morphology and viability remained unimpaired at all concentrations. Transmission electron microscopy showed an modification dependant attachment of nanoparticles to the cell membrane of spermatozoa, but provided no evidence for nanoparticle entrance into sperm cells. A molecular examination revealed a reduction of free thiol residues on the cell membrane after nanoparticle exposure, which could explain the decrease in sperm motility. Sperm fertilising ability decreased after exposure to 10 µg/ml of ligand-free nanoparticles indicating that agglomerated ligand-free nanoparticles interfere with membrane properties necessary for fertilisation. In conclusion, nanoparticles may impair key sperm functions solely by interacting with the sperm surface membrane.